Comparison of conventional flat-plate solar collector and solar boosted heat pump using unglazed collector for hot water production in small slaughterhouse - Chatchawan Chaichana (2018)
This study presents simulated results of solar water heating systems in a small slaughterhouse using two techniques. The first one is a normal solar water heating system using a flat-plate solar collector and the second one uses a solar-boosted heat pump system having a corrugated metal sheet roof as a solar collector. The number of solar collector units is between 1 and 5, and the volume of water in a storage tank is 300-1200 L. The heat pump in this work uses refrigerant mixture R22:R124:R152a of 20%:57%:23% as the working fluid. The weather conditions of Chiang Mai, Thailand, are taken as the input data. In the case of the normal solar water heating system, the shortest payback periods for 300, 600, 900, and 1200 L water are 3.63, 3.12, 2.95, and 2.82 yr, respectively. The suitable number of collectors for 300 L water is 1 unit with 600-900 L water storage; 2 units of collectors is suitable in the case of 1200 L water, and 3 units of collectors gives the shortest payback period. However, in the case of a solar heat pump system, the suitable payback periods for 300, 600, 900, and 1200 L water are 2.74, 1.79, 1.83, and 1.88 yr, respectively. In our case, 1 unit of this collector gives the shortest payback period.